Mantenimiento de centrales telefónicas tipo PBX. - Montaño Aguilera, Joffre Patricio (2013)
The public telephony consists on one from the biggest nets of telecommunications to world level, and he/she will take as introductory example, to the effects of presenting the basic concepts of telephony. Their architecture consists on several components, specialized in different functions, having as the main one, to connect terminals or users to each other, by means of the commutation functions, those that are carried out in "central of commutation." The public phone nets in their infrastructure are conformed by one: Net trounce, primary Net, secondary Net and the Net of subscribers. The infrastructure of a phone net is completed with the respective canalization, wired, closets, insulating material and it stops connections, among others. The phone nets for buildings are carried out based on the applicant's demands, strictly related with the norms and technical specifications specified by the National Corporation of Telecommunications. The secondary net is represented by the cables multipares that are used in the buildings, the dispersion net or of subscribers it is the horizontal net of each one of the plants and the primary net is the phone assault of the building. A centrally or PBX is that which connects the entrance lines coming from the public net with the internal extensions the buildings. Becoming this way a basic part of the infrastructure of communications of all the buildings of companies and public entities. With the desire of contributing with the correct operation and acting of the central PBX, installed in the Area of the Energy, the Industries and the Natural Resources Not Renewable; of the NATIONAL UNIVERSITY OF LOJA, in the present possible flaws are detailed that they can arise to hardware level or software, as well as the procedures and practical advice to continue for the arrangement of the same ones, depending on the failure type arisen in the centrally. The KIT PROSKIT PK - 4019A, it contains all the necessary implement’s to carry out works of maintenance of the preventive type and corrective at hardware level, as: telephone to verify the state of the lines, a line follower, pliers, among others. It is important to keep in mind that before carrying out an inspection or maintenance, the one in charge should be aware of the operation of the centrally or to have read the maker's manual, besides being familiarized with the maintenance team, to guarantee the perfect operation of the team installed PBX.